Reshaping our world: Collaborating with children for community-based climate change action. Issue 1 (March 2019) - Trott, Carlie D
This paper documents a collaborative, multi-site participatory action research project in collaboration with children to act on climate change within local community settings. The project was an after-school program that combined hands-on climate change educational activities with photovoice, a participatory action research method that uses digital photography as the basis for problem identification, group dialogue, and social change action. Grounded in transformative sustainability learning theory and integrated with an arts-based participatory action research methodology, the program was designed to strengthen children's climate change awareness and sense of agency through youth-led action projects. After describing the program, this article details the collaborative action projects designed and carried out by 10- to 12-year-olds in each community (e.g., policy advocacy, tree-planting, community garden) as well as how the program facilitated children's constructive climate change engagement through children's enjoyment and agentic action. The critical importance of participatory process and collaborative action in strengthening children's sense of agency is discussed.